Human Rights Abused in Qatar: FIFA Puts World Cup More Than Lives? - Alfarizi, Mohammad Hanaan; Morgan, Kirthie Rubini; Lago, Manuel Campos (Universitas Muhammadiyah Yogyakarta, 2023)
FIFA World Cup Largest Event, held in Qatar in 2022, is considered to have violated the human rights of many migrant workers, most of whom come from South Asia. As many as 6500 workers died because of the lack of security and supplies for workers. The Kafala Sponsorship System is also considered a source of problems. This research aims to determine who should be responsible for this case and what should be done. The research method used was normative juridical using various secondary sources such as books, journals and legislation. FIFA and Qatar are the ones who should be held responsible for this case because they pay little attention to the condition of migrant workers. In this case, FIFA and Qatar must immediately carry out investigative efforts and preventative measures.